Quintic Quandary

Algebra Level 3

If a quintic equation with a non-zero triple root p p and a non-zero double root q q has no x 2 x^2 term in its expanded form, then the ratio of p q = a ± b \dfrac{p}{q} = -a \pm \sqrt{b} for some integers a a and b b . Find a + b a + b .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Jordan Cahn
Jan 16, 2019

By Vieta's formulas , the coefficient of x 2 x^2 the sum of all triple products of roots. Thus ( 3 3 ) ( 2 0 ) p 3 + ( 3 2 ) ( 2 1 ) p 2 q + ( 3 1 ) ( 2 2 ) p q 2 = 0 All ways to choose three roots p 3 + 6 p 2 q + 3 p q 2 = 0 ( p q ) 2 + 6 p q + 3 = 0 Multiply by 1 p q 2 \begin{aligned} {3 \choose 3}{2 \choose 0}p^3 + {3\choose 2}{2\choose 1}p^2q + {3\choose 1}{2\choose 2}pq^2 &= 0 && \color{#3D99F6}\text{All ways to choose three roots} \\ p^3 + 6p^2q+3pq^2 &= 0 \\ \left(\frac{p}{q}\right)^2 + 6\frac{p}{q} + 3 &= 0 && \color{#3D99F6}\text{Multiply by }\frac{1}{pq^2}\end{aligned} p q = 6 ± 6 2 12 2 Apply the quadratic formula p q = 3 ± 6 \begin{aligned} \frac{p}{q} &= \frac{-6\pm\sqrt{6^2-12}}{2} && \color{#3D99F6}\text{Apply the quadratic formula} \\ \frac{p}{q} &= -3\pm\sqrt{6} \end{aligned} Thus a = 3 a=3 and b = 6 b=6 , giving us a + b = 3 + 6 = 9 a+b=3+6=\boxed{9} .

Nice solution!

David Vreken - 2 years, 4 months ago
Pi Han Goh
Jan 22, 2019

Let f ( x ) f(x) denote the monic polynomial equation in question, then f ( x ) = ( x p ) 3 ( x q ) 2 f(x) = (x-p)^3 (x-q)^2 , where p q p \ne q .

Since the coefficient of (the expanded form of) x 2 x^2 in f ( x ) f(x) is 0, then the coefficient of the constant in f ( x ) f''(x) must be 0 as well. As such, f ( x ) f''(x) has a root of 0.

By chain rule , f ( x ) = 3 ( x p ) 2 ( x q ) 2 + 2 ( x p ) 3 ( x q ) f ( x ) = 6 ( x p ) ( x q ) 2 + 6 ( x p ) 2 ( x q ) + 6 ( x p ) 2 ( x q ) + 2 ( x p ) 3 . f'(x) = 3(x-p)^2 (x-q)^2 + 2(x-p)^3 (x-q) \quad \implies \quad f''(x) = 6(x-p)(x-q)^2 + 6(x-p)^2 (x-q) + 6(x-p)^2 (x-q) + 2(x-p)^3.

With f ( 0 ) = 0 f''(0) = 0 , the equation above simplifies to 2 p ( p 2 + 6 p q + 3 q 2 ) = 0 -2p(p^2 + 6pq + 3q^2) = 0 . Since p 0 p\ne 0 , p 2 + 6 p q + 3 q 2 = 0 ( p q ) 2 + 6 ( p q ) + 3 = 0. p^2 + 6pq + 3q^2 = 0 \quad \implies \quad \left(\frac pq\right)^2 + 6\left( \frac pq\right) + 3 = 0. Using the quadratic formula , p q = 3 ± 6 \frac pq = -3\pm \sqrt 6 . Our answer is 3 + 6 = 9 3 + 6 = \boxed9 .

Chew-Seong Cheong
Jan 17, 2019

The quintic equation is therefore,

( x p ) 3 ( x q ) 2 = 0 ( x 3 3 p x 2 + 3 p 2 x p 3 ) ( x 2 2 q x + q 2 ) = 0 \begin{aligned} (x-p)^3(x-q)^2 & = 0 \\ (x^3-3px^2+3p^2x - p^3)(x^2-2qx+q^2) & = 0 \end{aligned}

Then the coefficient of x 2 x^2 is:

3 p q 2 6 p 2 q p 3 = 0 Multiply both sides by 1 p q 2 3 + 6 p q + p 2 q 2 = 0 Rearrange ( p q ) 2 + 6 p q + 3 = 0 Solve the quadratic for p q p q = 3 ± 6 \begin{aligned} - 3pq^2 -6p^2q - p^3 & = 0 & \small \color{#3D99F6} \text{Multiply both sides by }-\frac 1{pq^2} \\ 3 + 6\frac pq + \frac {p^2}{q^2} & = 0 & \small \color{#3D99F6} \text{Rearrange} \\ \left(\frac pq\right)^2 + 6 \frac pq + 3 & = 0 & \small \color{#3D99F6} \text{Solve the quadratic for }\frac pq \\ \implies \frac pq & = - 3 \pm \sqrt 6 \end{aligned}

Therefore, a + b = 3 + 6 = 9 a+b=3+6 = \boxed 9 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...